PENGUATAN KESADARAN HUKUM MASYARAKAT TERHADAP BAHAYA INVESTASI ILEGAL DAN SKEMA PONZI - Arif Fikri; Sawaluddin Siregar; J.B. Nicudemus Malindir; Sinarianda Kurnia Hartantien (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
Illegal investments and Ponzi schemes pose a serious threat to the financial security of communities, particularly in rural areas and small towns, as residents often lack adequate legal understanding regarding investment mechanisms and consumer protection. This community service activity aims to enhance public legal awareness concerning the risks of illegal investments and Ponzi schemes through outreach, legal education, and practical assistance based on applicable regulations. The methods employed include participatory training, workshops, case studies, and simulations for identifying illegal investment schemes, complemented by legal consultation for participants. Data were collected through participatory observation, pre- and post-test questionnaires, in-depth interviews, and analysis of legal documents related to investment and consumer protection. The results indicate a significant improvement in participants’ understanding of the distinction between legal and illegal investments, the characteristics of Ponzi schemes, and the legal measures that can be taken when confronted with fraudulent investment practices. Participants also demonstrated enhanced capacity to critically analyze investment offers and make informed financial decisions. Short-term impacts are reflected in increased vigilance among community members toward suspicious investment offers, while long-term impacts are expected to reduce financial losses and foster a culture of legal compliance. These findings confirm that practice- and regulation-based legal education is effective in strengthening community legal literacy related to investments and provides a substantial contribution to consumer protection and local economic stability.